2005
DOI: 10.1128/aac.49.12.5127-5128.2005
|View full text |Cite
|
Sign up to set email alerts
|

Pitfalls in Estimating Piperaquine Elimination

Abstract: By using a sensitive new assay, the terminal elimination half-life of the antimalarial piperaquine in a healthy volunteer was estimated to be 33 days, which is longer than estimated previously. This result illustrates the importance of extended sampling duration and sensitive assay methodologies in characterizing the disposition of slowly eliminated antimalarial drugs.The bisquinoline piperaquine (PQ) has been used as an antimalarial for decades in China, replacing chloroquine as the first-line treatment for P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
58
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 66 publications
(66 citation statements)
references
References 8 publications
5
58
3
Order By: Relevance
“…6 and suggests a terminal elimination half-life of 53 days. Assuming that the metabolite formation limits the elimination (i.e., formation rate limiting kinetics), this would support recent findings that the previously reported elimination half-life of PQ might be underestimated (Tarning et al, 2005). Further studies in larger series are needed to investigate the pharmacological and pharmacokinetic properties of this metabolite.…”
Section: Human Urinary Metabolites Of the Antimalarial Piperaquinesupporting
confidence: 69%
See 1 more Smart Citation
“…6 and suggests a terminal elimination half-life of 53 days. Assuming that the metabolite formation limits the elimination (i.e., formation rate limiting kinetics), this would support recent findings that the previously reported elimination half-life of PQ might be underestimated (Tarning et al, 2005). Further studies in larger series are needed to investigate the pharmacological and pharmacokinetic properties of this metabolite.…”
Section: Human Urinary Metabolites Of the Antimalarial Piperaquinesupporting
confidence: 69%
“…Only M1 and M2 were detected in the analyzed serum/plasma samples; therefore, these are the most clinically relevant metabolites. Blood and plasma were collected for up to 93 days and urine for 123 days, and PQ pharmacokinetics was evaluated as previously reported (Tarning et al, 2005(Tarning et al, , 2006. Reanalyzed urine contained substantial amounts of M1 and M2.…”
Section: Human Urinary Metabolites Of the Antimalarial Piperaquinementioning
confidence: 99%
“…One study in healthy adults found that, although a three-compartment model represented the postadministration profile better, there were insufficient data to support its use over a two-compartment model (38). The mean elimination t 1/2 , a parameter influenced by the duration of sampling (45), was 512 h, a value within the previously reported range of 224 to 667 h (1,14,25,28,31,34,38,44). Since there was substantial variability in the absorption phase of the plasma PQ concentration profile, a transit compartment model was tested and proved better than simpler absorption models that used lag time, as has been found in studies of other drugs (39).…”
Section: Discussionmentioning
confidence: 99%
“…Piperaquine (PIP), a bisquinoline antimalarial (1,3-bis [1-(7-chloro-4 quinolyl)-4 piperazinyl]-propane), has a similar mode of action to other quinoline antimalarials: interference with haem detoxification (Davis et al, 2005). It has pharmacokinetic properties similar to chloroquine with a very large apparent volume of distribution and a very long terminal elimination half-life Tarning et al, 2005). Piperaquine has been used extensively only in China, where it replaced chloroquine as first-line treatment in 1978.…”
Section: Introductionmentioning
confidence: 99%